Attempts to rationalize protein crystallization using relative crystallizability - Zhu, D.-W.; Garneau, A.; Mazumdar, M.; Zhou, M.; Xu, G.-J.; Lin, S.-X. (Journal of structural biology, 2006)
Protein crystal growth (PCG) remains the bottleneck of crystallography despite many decades of study. The nucleation zone in the two-dimensional-phase diagram has been used to evaluate the relative crystallizability of proteins, which is expressed as a percentage over the phase area delineated by experimental protein and precipitating agent concentration ranges. For protein-salts which are subject to a direct temperature effect on solubility, as represented by Egg Lysozyme, a decrease in temperature augments the nucleation zone percentage whereas for those with retrograde solubility as a function of temperature, for example fructose-1,6-bisphosphatase in the presence and absence of AMP, an increase in temperature can significantly enhance the relative crystallizability. These results have been confirmed by the number of “hits” using PEGs as precipitating agents in Sparse Matrix Screen experiments for different proteins and are in excellent agreement with the relative crystallizability. The relationship between solubility dependence, relative crystallizability and crystallization success, has been evidenced. Such crystallizability can become a guide to identify efficient crystallization regions, providing a rational approach to PCG and structural biology.